Dissecting the biophysical mechanisms underlying regeneration of complex organs in vertebrates - Monteiro, Joana (2015)
Tese de doutoramento, Ciências Biomédicas (Ciências Morfológicas), Universidade de Lisboa, Faculdade de Medicina, 2014